Intestinal Obstructions - Victorovich Garbuzenko, Dmitry (IntechOpen, 2020)
A group of pathological conditions characterized by the impaired passage of contents from the stomach to the rectum as well as the intestinal obstruction is associated with a very severe course, difficulty in diagnosis, and an unfavorable outcome. Mechanical intestinal obstruction is a current problem of emergency abdominal surgery and affects both the small and large bowels. This book, Intestinal Obstructions, presents information on small bowel obstruction and large bowel obstruction and their various causes, including adhesions, hernias, neoplasms, cancers, drugs, trauma, and others.